The Importance Of Love In Life In Eloisa James's When Beauty Tamed The Beast Novel (2011): A HuManistic Psychological Approach - Ermawati, Novia Candra, Drs. M. Thoyibi, M.S, Siti Fatimah, S.pd, M.Hum (2013)
This study is proposed to reveal how is the importance of loving in life reflected in Eloisa James's When Beauty Tamed The Beast novel which is published in 2011. The object of the study is When Beauty Tamed The Beast novel written by Eloisa James. The objectives of the study are to analyze the structural elements in the novel and to analyze the importance of love in life based on humanistic psychological approach. The writer employs the descriptive qualitative research as type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is When Beauty Tamed The Beast novel and secondary data source is information theory including references and materials related to the stud y whether picking up from books and internet. The techniques of collecting data are observation and library review. The technique of analyzing data is descriptive technique. Based on the analysis, the researcher draw two conclusions: first, based on the st ructural analysis, Eloisa James wants to deliver a moral message that love is willing to accept other as they are. Second, based on the humanistic psychological analysis, Eloisa James describes a psychological phenomenon of a person fulfilling the love and belongingness needs represented by Piers Yelverton's love and belongingness needs